A Revolution in Television and a Great Leap Forward for Innovation?: China in the Global Television Format Business - Keane, Michael (Global Television Formats : Circulating Culture, Producing Identity, 2012)
Livre : For decades, television scholars have viewed global television through the lens of cultural imperialism, focusing primarily on programs produced in the US and UK markets and exported to foreign markets. This book explores how, thanks to recent technological innovation and globalization, television is now finally becoming truly global. Global Television Formats aims to revise the place of the global in television studies. The essays gathered here explore the diversity of global programming and approaches, and ask how to theorize contemporary
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

NZ Idol: Nation Building Through Format Adaptation - De Bruin, Joost (Global Television Formats: Understanding Television Across Borders, 2012)
Three seasons of NZ Idol , the New Zealand adaptation of the global Idols format, were aired on public broadcaster TVNZ’s channel TV2 in 2004, 2005 and 2006. The ﬁnal episode of the ﬁrst season was the most-watched television programme in New Zealand in 2004, with 1.4 million people, a third of the New Zealand population, tuning in (South Paciﬁc Pictures, 2004). In terms of ratings NZ Idol has been one of the most successful locally made television programmes of the last decade. At ﬁrst glance, NZ Idol has also been very successful in representing ethnic and cultural diversity. In the auditions phase of the show young New Zealanders of 16 years plus from a range of backgrounds are featured, and in the subsequent phases the audience gets to know a selection of them intimately. The winners of all three seasons (Ben Lummis in season 1, Rosita Vai in season 2, and Matt Sounoa in season 3) have Paciﬁc Island roots, and as a result three young “brown” people were crowned “New Zealand Idols.” This is remarkable, since according to a previous study by Misha Kavka (2004: 231) non-white people have largely been absent from New Zealand reality TV programmes. A closer look suggests, however, that featuring contestants from different cultural backgrounds in NZ Idol generally serves a particular nation building agenda that New Zealand is heavily involved in as a postcolonial society, in which ethnic minorities are subjected to representations that favour the interests of dominant cultural groups. The aim of this nation building agenda is to establish a new and distinct sense of national identity which will set New Zealand apart from Britain, the former colonial power, and other English-speaking nations.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); Aotearoa/Nouvelle-Zélande (corpus analysé); Aotearoa/Nouvelle-Zélande (lieu de production du savoir); _Nettoyé